A catalyst and preparation method thereof, and a method for catalyzing methanol to prepare ethylene oxide

By using anatase-type titanium dioxide (001) single-crystal thin film catalyst covering the crystal surface of strontium titanate (001), the energy consumption and by-product problems of the multi-step reaction process of ethylene oxide production in the prior art are solved, and the energy consumption and by-product problems of ethylene oxide production in the prior art are achieved. An efficient method for preparing ethylene oxide in one step by methanol.

CN115999529BActive Publication Date: 2025-02-07UNIV OF SCI & TECH OF CHINA
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202211672738.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-12-26
Publication Date
2025-02-07
Estimated Expiration
2042-12-26

AI Technical Summary

Technical Problem

In the prior art, the multi-step reaction process of producing ethylene oxide consumes a large amount of energy and produces a large number of by-products, resulting in low production costs and yields.

Method used

Using anatase-type titanium dioxide (001) single crystal thin film covered with strontium titanate (001) crystal surface as a catalyst, the catalyst was prepared under ultra-high vacuum and oxygen atmosphere by pulsed laser deposition technology, and used to catalyze the direct preparation of epoxy by methanol. Ethane.

Benefits of technology

The preparation of ethylene oxide in one step using methanol as raw material is achieved, reducing energy consumption, improving yield, good catalyst stability, fewer by-product types, and low reaction conditions requirements.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115999529B_ABST
    Figure CN115999529B_ABST
Patent Text Reader

Abstract

The present disclosure proposes a catalyst, including: a strontium titanate (001) crystal plane, and an anatase titanium dioxide (001) single crystal film covering the strontium titanate (001) crystal plane. There is a lattice difference between the strontium titanate (001) crystal plane and the anatase titanium dioxide (001) single crystal film, and it has the activity of atomic charge transfer. The present disclosure also proposes a preparation method thereof, including: under a first temperature condition, using titanium dioxide powder as a target material, in an atmosphere of ultra-high vacuum and oxygen, using pulsed laser deposition technology to sputter and coat the strontium titanate (001) crystal plane, and keeping the temperature in an oxygen environment for a first time range. The present disclosure also proposes a method for catalyzing methanol to directly prepare ethylene oxide, including: under a second temperature condition, placing the catalyst in methanol gas to activate for a second time range, maintaining the second temperature, continuing to introduce methanol gas, and dehydrogenating methanol to obtain ethylene oxide.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to the field of catalytic materials and chemical technology, and in particular to a catalyst for efficiently catalytically converting methanol into ethylene oxide, and a preparation method and application thereof. Background Art

[0002] Ethylene oxide is a precursor of ethylene glycol, glycol ether, epoxy resin and many industrial chemicals and plastic polymers, and has important application value in the chemical industry. At present, the main method for producing ethylene oxide is to use silver-loaded alumina as an industrial catalyst to synthesize ethylene by oxidation, and ethylene is obtained by petroleum cracking or methanol to olefins (MTO) reaction. Therefore, the synthesis of ethylene oxide from chemical raw material methanol usually requires the synthesis of ethylene first, and then the epoxidation of ethylene oxide. Such a multi-step reaction process consumes a lot of energy and produces a large amount of carbon dioxide and other by-products, which greatly affects the production cost and yield of ethylene oxide.

[0003] Therefore, finding an efficient catalyst that can directly prepare ethylene oxide from methanol is a scientific and technological problem that needs to be urgently solved in the chemical industry and by front-line researchers. Summary of the invention

[0004] In view of this, in order to simplify the preparation process of ethylene oxide, improve the yield of ethylene oxide, and reduce production costs, the present disclosure proposes a catalyst and a preparation method, as well as a method for catalyzing methanol to prepare ethylene oxide.

[0005] In a first aspect of the present disclosure, a catalyst is provided, comprising:

[0006] Anatase titanium dioxide (001) single crystal thin film covering the strontium titanate (001) crystal plane;

[0007] Among them, there is a lattice difference between the strontium titanate (001) crystal plane and the anatase titanium dioxide (001) single crystal film, which has surface tension.

[0008] According to the embodiment of the present disclosure, the ratio of the lattice difference ranges from 3% to 5%.

[0009] According to the embodiment of the present disclosure, the thickness of the anatase titanium dioxide (001) single crystal film is 10 nm to 25 nm.

[0010] According to an embodiment of the present disclosure, the catalyst further includes nano-crystals having an anatase-strontium titanate shell structure.

[0011] According to the embodiment of the present disclosure, the nano-crystals having an anatase-strontium titanate shell structure are obtained by chemical synthesis or by epitaxially growing an anatase-type titanium dioxide (001) encapsulating layer outside the strontium titanate nano-crystals to obtain the shell structure.

[0012] In a second aspect of the present disclosure, a method for preparing a catalyst is provided, comprising the following steps:

[0013] Under the first temperature condition, pulse laser deposition technology is used to sputter coat the strontium titanate (001) crystal surface. Titanium dioxide powder is used as the target material of the pulse laser technology. Titanium dioxide clusters are laser deposited onto the strontium titanate (001) surface in an ultra-high vacuum and oxygen atmosphere. The catalyst is obtained by keeping the temperature in an oxygen environment for a first time range.

[0014] According to the embodiment of the present disclosure, the deposition rate of the pulsed laser deposition technology is 0.5 to 1.5 nm / hour, and the deposition time is 10 to 25 hours.

[0015] According to an embodiment of the present disclosure, the first temperature range is 800-900K, and the first time range is 1-2h.

[0016] According to the embodiment of the present disclosure, the ultra-high vacuum atmosphere is a vacuum chamber with a vacuum pressure higher than 1×10 -9 mbar.

[0017] According to the embodiment of the present disclosure, the pressure of oxygen is 5×10 -3 mbar~1×10 -2 mbar, oxygen purity is higher than 99.99%.

[0018] According to an embodiment of the present disclosure, the titanium dioxide powder is a titanium dioxide powder material with a purity higher than 99.9%.

[0019] In a third aspect of the present disclosure, a method for preparing ethylene oxide by catalyzing methanol using the above catalyst is provided, comprising the following steps:

[0020] Under a second temperature condition, placing the catalyst in methanol gas for activation for a second time range;

[0021] The second temperature is maintained, and methanol gas is continuously introduced to perform dehydrogenation cyclization of methanol to obtain ethylene oxide.

[0022] According to an embodiment of the present disclosure, the second temperature range is 550K to 590K, and the second time range is 1 to 2 hours.

[0023] According to the embodiment of the present disclosure, methanol gas uses nitrogen as a carrier gas, wherein the purity of methanol gas is higher than 99% and the partial pressure is 1×10 -3 mbar~10mbar.

[0024] The catalyst and preparation method thereof and the method for preparing ethylene oxide by catalyzing methanol proposed in the present disclosure have one or part of the following beneficial effects:

[0025] (1) According to the embodiments of the present disclosure, the present disclosure selects the anatase phase titanium dioxide (001) crystal plane with high catalytic activity, and uses the strontium titanate (001) crystal plane with a similar lattice structure as the substrate. Due to the slight lattice difference between the substrate strontium titanate (001) crystal plane and the anatase phase titanium dioxide (001) crystal plane, there is a certain surface tension between the two phases. Under the action of this tension, the anatase phase titanium dioxide has excellent catalytic performance. The core mechanism of the catalytic performance of the present disclosure is that the surface tension enhances the catalytic performance of the anatase phase titanium dioxide.

[0026] (2) According to the embodiments of the present disclosure, the catalyst prepared by the present disclosure can realize the one-step preparation of ethylene oxide using methanol as raw material, reducing the energy consumption of the traditional multi-step reaction and improving the yield of methanol to ethylene oxide. In the catalytic process, the catalyst proposed in the present disclosure has good stability, few types of catalytic by-products, and low requirements for catalytic reaction conditions. It is an efficient catalyst and application method for catalyzing methanol to prepare ethylene oxide. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 is a high-resolution electron microscopy image of the side surface of anatase titanium dioxide (001) single crystal thin film in the present disclosure;

[0028] Figure 2 is an atomic-level morphology of the surface of anatase titanium dioxide (001) in the present disclosure;

[0029] Figure 3 is a possible morphological structure diagram of nano-grains of anatase-strontium titanate shell structure in the present disclosure;

[0030] Figure 4 is a schematic diagram of the cross-sectional structure of the nano-grains of anatase-strontium titanate shell structure disclosed in the present invention;

[0031] Figure 5 is a process flow chart for preparing a catalyst and preparing ethylene oxide in the present disclosure;

[0032] Figure 6 is a mass spectrum of ethylene oxide molecules desorbed from the surface of anatase titanium dioxide (001) single crystal thin film prepared in the present disclosure;

[0033] Figure 7 It is a relationship diagram between the number of times the catalyst is used and the ethylene oxide conversion rate in the present disclosure. DETAILED DESCRIPTION

[0034] In order to make the objectives, technical solutions and advantages of the present disclosure more clearly understood, the present disclosure is further described in detail below in combination with specific embodiments and with reference to the accompanying drawings.

[0035] The endpoints and any values ​​of the ranges disclosed in this disclosure are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, and these numerical ranges should be regarded as specifically disclosed in this disclosure.

[0036] In the process of realizing the present disclosure, it is found that the multi-stage reaction to prepare ethylene oxide not only consumes a lot of energy, but also produces a variety of by-products, reducing the yield of ethylene oxide. Therefore, it is of far-reaching significance to find an efficient catalyst to prepare ethylene oxide in one step using methanol as a raw material.

[0037] Studies have shown that anatase titanium dioxide has high catalytic performance, but in practical applications, it is found that single anatase titanium dioxide is difficult to directly catalyze methanol to produce ethylene oxide.

[0038] Figure 1 A high-resolution electron microscope image of the side surface of anatase-type titanium dioxide (001) single crystal thin film in the catalyst disclosed in the present invention is schematically shown.

[0039] Figure 2 The atomic-level morphology of the surface of anatase titanium dioxide (001) in the present disclosure is schematically shown.

[0040] In a first aspect of the present disclosure, a catalyst is provided, comprising:

[0041] SrTiO3 (001) crystal plane, and

[0042] Structure Figure 1 As shown, anatase titanium dioxide (001) single crystal thin film covered on the strontium titanate (001) crystal plane;

[0043] Among them, the atomic morphology of the (001) crystal plane of anatase titanium dioxide is as follows: Figure 2 As shown, there is a lattice difference between the strontium titanate (001) crystal plane and the anatase titanium dioxide (001) single crystal film, which has surface tension.

[0044] According to the embodiments of the present disclosure, the present disclosure selects the anatase phase titanium dioxide (001) crystal plane with high catalytic activity, and uses the strontium titanate (001) crystal plane with a similar lattice structure as the substrate. Among them, although the strontium titanate (001) crystal plane has no catalytic performance, due to the slight lattice difference between the substrate strontium titanate (001) crystal plane and the anatase phase titanium dioxide (001) film crystal plane, there is a certain surface tension between the two phases. Under the action of this tension, the anatase phase titanium dioxide has excellent catalytic performance. The surface tension enhancing the catalytic performance of the anatase phase titanium dioxide is the core mechanism of the catalytic performance of the present disclosure.

[0045] According to the embodiment of the present disclosure, the ratio of the lattice difference ranges from 3% to 4%.

[0046] According to the embodiments of the present disclosure, the lattice difference is within this range, has a larger surface tension, and can activate the catalytic performance of anatase phase titanium dioxide to the greatest extent.

[0047] According to the embodiment of the present disclosure, Figure 1 As shown, the thickness of the anatase titanium dioxide (001) single crystal film is 10 nm to 25 nm.

[0048] According to the embodiments of the present disclosure, the thickness of the anatase titanium dioxide (001) single crystal film is within this range and has a surface tension that can activate the catalytic properties of the anatase phase titanium dioxide to the maximum extent. If the thickness of the anatase titanium dioxide (001) single crystal film is too large or too small, the surface tension will be lost.

[0049] Figure 3 The possible morphological structure diagram of the nano-grains of anatase-strontium titanate shell structure in the present disclosure is schematically shown.

[0050] According to an embodiment of the present disclosure, the catalyst further includes nano-crystals having an anatase-strontium titanate shell structure.

[0051] According to the embodiment of the present disclosure, Figure 3 As shown, including but not limited to Figure 3 Four nanoparticles are shown, in which the catalytic performance is concentrated on the anatase TiO2 (001) crystal plane.

[0052] Figure 4 The cross-sectional structure diagram of the nano-grains of anatase-strontium titanate shell structure in the present disclosure is schematically shown.

[0053] According to the embodiment of the present disclosure, Figure 4 As shown, the nanoparticles with anatase-strontium titanate shell structure are obtained by chemical synthesis or epitaxial growth of anatase-type titanium dioxide (001) wrapping layer outside the strontium titanate nanoparticles to obtain the shell structure.

[0054] According to the embodiment of the present disclosure, strontium titanate nanoparticles are used as the inner layer structure, and anatase-type titanium dioxide (001) wrapping layer is epitaxially grown to produce a catalytic effect.

[0055] Figure 5 The process flow chart of preparing the catalyst and preparing ethylene oxide in the present disclosure is schematically shown. In a second aspect of the present disclosure, a method for preparing the catalyst is proposed, comprising the following steps:

[0056] like Figure 5As shown, under the first temperature conditions, pulsed laser deposition technology is used to sputter coat the strontium titanate (001) crystal surface, titanium dioxide powder is used as the target material of the pulsed laser technology, and titanium dioxide clusters are laser deposited onto the strontium titanate (001) surface in an ultra-high vacuum and oxygen atmosphere, and the catalyst is obtained by keeping the temperature in an oxygen environment for a first time range.

[0057] According to the embodiments of the present disclosure, the pulsed laser deposition technology is used to ensure that the composition of the thin film and the target material is consistent. The rapid action of the laser and the target material completes the thermal melting and evaporation in a short time, and also ensures that no phase separation occurs within the laser irradiation range, thereby completing the deposition of catalytic anatase phase titanium dioxide onto a material with a strontium titanate substrate.

[0058] According to the embodiment of the present disclosure, the deposition rate of the pulsed laser deposition technology is 0.5 to 1.5 nm / hour, and the deposition time is 10 to 25 hours.

[0059] According to an embodiment of the present disclosure, the first temperature range is 800-900K, and the first time range is 1-2h.

[0060] According to the embodiments of the present disclosure, during the pulsed laser deposition process, substrate temperature is one of the key factors affecting the anatase phase titanium dioxide (001) film. Too high a temperature will cause the anatase phase titanium dioxide to transform into the rutile phase.

[0061] According to the embodiment of the present disclosure, the ultra-high vacuum atmosphere is a vacuum chamber with a vacuum pressure higher than 1×10 -9 mbar.

[0062] According to the embodiments of the present disclosure, the vacuum background can reduce the impurity content of the anatase titanium dioxide (001) single crystal thin film during the pulsed laser deposition process.

[0063] According to the embodiment of the present disclosure, the pressure of oxygen is 5×10 -3 mbar~1×10 -2 mbar, oxygen purity is higher than 99.99%.

[0064] According to the embodiment of the present disclosure, it is necessary to ensure that the oxygen pressure remains constant during sputtering.

[0065] According to an embodiment of the present disclosure, the titanium dioxide powder is a titanium dioxide powder material with a purity higher than 99.9%.

[0066] In a third aspect of the present disclosure, a method for preparing ethylene oxide by catalyzing methanol using the above catalyst is provided, comprising the following steps:

[0067] like Figure 5 As shown, under the second temperature condition, the above catalyst is placed in methanol gas for activation for a second time range;

[0068] The second temperature is maintained, and methanol gas is continuously introduced to perform dehydrogenation cyclization of methanol to obtain ethylene oxide.

[0069] According to the embodiments of the present disclosure, the catalyst prepared by the present disclosure can realize the one-step preparation of ethylene oxide using methanol as raw material. In the catalytic process, the catalyst has good stability, few types of catalytic byproducts, low requirements for catalytic reaction conditions, reduced energy consumption, and increased yield. It is an efficient catalyst and application method for catalyzing methanol to prepare ethylene oxide.

[0070] According to the embodiments of the present disclosure, the by-products of the method for preparing ethylene oxide from methanol using the above catalyst in the present disclosure are mainly acetaldehyde, acetic acid and methyl acetate.

[0071] According to an embodiment of the present disclosure, the second temperature range is 550K to 590K, and the second time range is 1 to 2 hours.

[0072] According to the embodiment of the present disclosure, methanol gas uses nitrogen as a carrier gas, wherein the purity of methanol gas is higher than 99% and the partial pressure is 1×10 -3 mbar~10mbar.

[0073] According to the embodiments of the present disclosure, nitrogen is low-cost and does not react with the catalyst, such as Figure 5 As shown, ethylene oxide can also be prepared in a pure methanol atmosphere in the laboratory.

[0074] It should be noted that the described embodiments are only part of the embodiments of the present disclosure, rather than all of the embodiments. Based on the embodiments of the present disclosure, other embodiments obtained by ordinary technicians in the field without creative work are all within the scope of protection of the present disclosure.

[0075] It should be noted that, unless otherwise defined, the technical terms or scientific terms used in the present disclosure shall have the usual meanings understood by persons with ordinary skills in the field to which the present disclosure belongs. If the full text involves descriptions such as "first", "second", etc., the descriptions such as "first", "second", etc. are only used to distinguish similar objects, and cannot be understood as indicating or implying their relative importance, order of precedence, or implicitly indicating the number of technical features indicated. It should be understood that the data described by "first", "second", etc. can be interchangeable under appropriate circumstances.

[0076] Example 1: Preparation of Catalyst

[0077] A 0.7wt% Nb-doped strontium titanate (SrTiO3, STO) (001) single crystal material with a size of 12mm×5mm×0.5mm was selected as the substrate. It was placed in acetone and ultrasonicated to remove organic impurities attached to the surface; deionized water was then ultrasonicated to remove inorganic impurities adsorbed on the surface. The cleaned strontium titanate (001) single crystal substrate was placed on a sample holder and introduced into an ultra-high vacuum preparation chamber, where the vacuum pressure in the vacuum chamber was higher than 1×10 -9 mbar. After being introduced into the preparation chamber, the surface of the strontium titanate (001) single crystal substrate is first degassed by direct current heating for about 1 hour, wherein the heating temperature range of the degassing treatment is 800K to 1000K. Then, the strontium titanate (001) single crystal substrate is subjected to argon ion etching for 30 minutes (argon ion energy is generally 1.5 to 2.0 keV) and vacuum annealing for 30 minutes (temperature is generally 800K to 1000K). The argon etching annealing treatment needs to be carried out for 3 to 5 cycles to ensure that the surface of the substrate after treatment can reach atomic level flatness.

[0078] Keeping the substrate temperature and oxygen pressure conditions unchanged, using TiO2 with a purity greater than 99% as the target, using the pulsed laser deposition method, focusing the pulsed laser on the target, sputtering TiO2 clusters onto the surface of the strontium titanate (001) single crystal substrate. After the preparation is completed, the obtained catalyst sample still needs to be heated in an oxygen pressure environment for 1 hour, and then cooled to room temperature to obtain an anatase-type titanium dioxide (001) single crystal film with a thickness of 10nm.

[0079] The parameters of the pulse laser are set to 248nm pulse laser, 4Hz frequency, and a single pulse energy of about 2 millijoules. During the deposition process, the substrate temperature needs to be maintained at 550K~590K, and oxygen is continuously introduced to maintain the oxygen pressure at 5×10 -5 ~1×10 -2 mbar.

[0080] In order to ensure the quality and uniformity of the anatase titanium dioxide (001) single crystal film, the laser spot needs to scan cyclically on the target during sputtering, and the target also rotates at a constant speed. The deposition rate of the film is controlled to be about 1nm / hour.

[0081] Example 2: Preparation of ethylene oxide using methanol as raw material using a catalyst

[0082] At room temperature, the catalyst in Example 1 was placed in a methanol atmosphere to activate the surface for 1 to 2 hours, wherein the methanol pressure was 1×10 -3 mbar~10mbar, with nitrogen as carrier gas.

[0083] After activation, methanol gas is introduced, and the catalyst surface catalyzes the coupling of methanol to generate ethylene oxide precursor. The ethylene oxide precursor adheres to the catalyst surface and desorbs from the catalyst surface in the form of ethylene oxide gas molecules under the condition of a substrate temperature of 550K to 590K.

[0084] Figure 6 The mass spectrum of ethylene oxide and the main by-product acetaldehyde desorbed from the surface of anatase titanium dioxide (001) single crystal film is schematically shown.

[0085] like Figure 6 As shown, the product under the condition of substrate temperature of 330K~380K is mainly acetaldehyde, and the product under the condition of substrate temperature of 550K~590K is mainly ethylene oxide.

[0086] After ethylene oxide is desorbed from the catalyst surface, new methanol molecules will continue to couple on the catalyst surface to continuously generate new ethylene oxide molecules. Therefore, the partial pressure of methanol gas is maintained at 1×10 -3 mbar~10mbar, and maintaining the temperature of the substrate at 550K~590K, ethylene oxide gas can be continuously generated and desorbed on the catalyst surface.

[0087] Test example: Stability test

[0088] Figure 7 The relationship between the yield and stability of the catalyst prepared in the examples of the present disclosure in 50 repeated catalytic experiments is schematically shown.

[0089] like Figure 7 As shown, the catalyst prepared in the embodiment of the present disclosure can still catalyze methanol to produce ethylene oxide after more than 50 tests, and its conversion rate is about 40%. It can be seen from the test that the catalyst has stable performance and good repeatability.

[0090] Similarly, the nanocrystals of anatase-strontium titanate (ATO-STO) shell structure prepared based on the principle of the present disclosure also fall within the scope of protection of the present disclosure. Among them, the structure of the ATO-STO nanocrystals is as follows: Figure 3 As shown. Nanocrystalline particles can be obtained by chemical synthesis or by epitaxially growing anatase (ATO) coating layer on the outside of strontium titanate (STO) crystal powder to form a shell structure. Nanocrystalline particles also have the performance of directly catalyzing methanol to ethylene oxide similar to the surface of anatase (ATO) (001) film epitaxially grown on the outside of strontium titanate (STO).

[0091] The specific embodiments described above further illustrate the purpose, technical solutions and beneficial effects of the present disclosure. It should be understood that the above description is only a specific embodiment of the present disclosure and is not intended to limit the present disclosure. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present disclosure should be included in the protection scope of the present disclosure.

Claims

1. A method for directly preparing ethylene oxide by catalyzing methanol, characterized in that: The method comprises the following steps: Under a first temperature condition, placing the catalyst in methanol gas for activation for a first time range; Maintaining the first temperature, continuing to introduce the methanol gas, and dehydrogenating and cyclizing the methanol to obtain ethylene oxide; The catalyst comprises a strontium titanate (001) crystal plane and an anatase titanium dioxide (001) single crystal film covering the strontium titanate (001) crystal plane; there is a lattice difference between the strontium titanate (001) crystal plane and the anatase titanium dioxide (001) single crystal film, and there is surface tension, and the ratio of the lattice difference ranges from 3% to 5%; the thickness of the anatase titanium dioxide (001) single crystal film is 10nm to 25nm.

2. The method according to claim 1, characterized in that: The first temperature range is 550K to 590K; The first duration ranges from 1 to 2 hours; The methanol gas uses nitrogen as a carrier gas, wherein the purity of the methanol gas is higher than 99% and the partial pressure is 1×10 -3 mbar~10 mbar.

3. The method according to claim 1, characterized in that: The catalyst also includes nano-crystals having an anatase-strontium titanate shell structure.

4. The method according to claim 3, characterized in that The nano-crystals with anatase-strontium titanate shell structure are obtained by chemical synthesis or by epitaxially growing anatase-type titanium dioxide (001) wrapping layer outside the strontium titanate nano-crystals to obtain the shell structure.

5. The method according to claim 1, characterized in that The preparation method of the catalyst comprises the following steps: Under the second temperature condition, a pulsed laser deposition technique is used to sputter-coat the strontium titanate (001) crystal surface, titanium dioxide powder is used as the target material of the pulsed laser technique, titanium dioxide clusters are laser deposited onto the strontium titanate (001) surface in an ultra-high vacuum and oxygen atmosphere, and the surface is kept warm in an oxygen environment for a second time range to obtain the catalyst.

6. The method according to claim 5, characterized in that The deposition rate of the pulse laser deposition technology is 0.5 to 1.5 nm / h, and the deposition time is 10 to 25 hours; The second temperature range is 800-900K; The second duration ranges from 1 to 2 hours.

7. The method according to claim 5, characterized in that The ultra-high vacuum atmosphere is a vacuum chamber with a vacuum pressure higher than 1×10 -9 mbar; The oxygen pressure is 5×10 -3 mbar~1×10 -2 mbar, oxygen purity is higher than 99.99%; The titanium dioxide powder is a titanium dioxide powder material with a purity higher than 99.9%.

Citation Information

Patent Citations

  • Method of preparing anatase-type tio2 single crystal thin film

    JP2001342022A